2006
DOI: 10.1074/jbc.m510934200
|View full text |Cite
|
Sign up to set email alerts
|

Myelin-associated Glycoprotein Inhibits Microtubule Assembly by a Rho-kinase-dependent Mechanism

Abstract: Myelin-associated glycoprotein (MAG) and Nogo are potent inhibitors of neurite outgrowth from a variety of neurons, and they have been identified as possible components of the central nervous system myelin that prevents axonal regeneration in the adult vertebrate central nervous system. The activation of RhoA and Rhokinase is reported to be an essential part of the signaling mechanism of these proteins. Here, we report that the collapsing response mediator protein-2 (CRMP-2) is phosphorylated by a Rho-kinasede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(103 citation statements)
references
References 39 publications
3
99
1
Order By: Relevance
“…This is partly mediated by binding to tubulin heterodimers and promoting microtubule assembly (Fukata et al, 2002b). In fact, CRMP2 undergoes ROCK-dependent phosphorylation in response to Nogo-66, and MAG and has been hypothesized to subsequently regulate microtubule dynamics (Mimura et al, 2006). Although all CRMP members can bind tubulin, CRMP4 is not a substrate for ROCK, and we were unable to detect a change in affinity between CRMP4 and tubulin in response to Nogo-66 stimulation by coimmunoprecipitation analysis in PC12 cells (data not shown).…”
Section: C4rip As a Therapeutic Agentmentioning
confidence: 38%
“…This is partly mediated by binding to tubulin heterodimers and promoting microtubule assembly (Fukata et al, 2002b). In fact, CRMP2 undergoes ROCK-dependent phosphorylation in response to Nogo-66, and MAG and has been hypothesized to subsequently regulate microtubule dynamics (Mimura et al, 2006). Although all CRMP members can bind tubulin, CRMP4 is not a substrate for ROCK, and we were unable to detect a change in affinity between CRMP4 and tubulin in response to Nogo-66 stimulation by coimmunoprecipitation analysis in PC12 cells (data not shown).…”
Section: C4rip As a Therapeutic Agentmentioning
confidence: 38%
“…This suggests that extracellular inhibitory molecules could also induce changes in the dynamics and morphology of the axonal tip by affecting microtubule organization. Indeed, a recent report from Mimura et al (2006) showed that MAG inhibits microtubule assembly and axon outgrowth in postnatal cerebellar granule neurons via Rho kinase activation. Interestingly, they identified CRMP-2 (collapsin response mediator protein-2), a microtubuleassociated protein, as a target for microtubule disassembly both in vitro and in vivo after spinal cord injury.…”
Section: Putative Signaling Mechanisms Underlying Microtubule Disorgamentioning
confidence: 99%
“…Microtubules are regulated by external signals during axon elongation and guidance (Suter et al, 1998;Buck and Zheng, 2002;Dent and Gertler, 2003). In fact, the known inhibitory cues present in the CNS myelin and the glial scar, including myelinassociated glycoprotein (MAG), Nogo, OMgP (oligodendrocytemyelin glycoprotein), and versican, converge downstream of their receptors onto signaling pathways of the Rho GTPases (Dubreuil et al, 2003;Fournier et al, 2003;Schweigreiter et al, 2004;Sivasankaran et al, 2004), which, in addition to the actin cytoskeleton, also affect microtubule stability and dynamics (Etienne-Manneville, 2004;Mimura et al, 2006). This suggests that extracellular inhibitory molecules could also induce changes in the dynamics and morphology of the axonal tip by affecting microtubule organization.…”
Section: Putative Signaling Mechanisms Underlying Microtubule Disorgamentioning
confidence: 99%
“…After disruption at the lesion site of the optic nerve, inhibitory factors from the myelin activate RhoA (Mukhopadhyay et al, 1994;Chen et al, 2000;GrandPre et al, 2000;Prinjha et al, 2000;Wang et al, 2002;Atwal et al, 2008) and further downstream cascades lead to a local arrest of axonal microtubule polymerization and axon extension (Mimura et al, 2006;Geraldo and Gordon-Weeks, 2009). The current study demonstrates that neurite growth inhibition of primary RGCs and PC12 cells by CNS myelin in culture is abolished in the presence of Taxol (3 nM).…”
Section: Taxol Overcomes Myelin and Cspg Inhibitionmentioning
confidence: 99%